2019
DOI: 10.20506/rst.38.2.2998
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of epizootic ulcerative syndrome on subsistence fisheries and wildlife

Abstract: Epizootic ulcerative syndrome (EUS), caused by the water mould (Oomycota) Aphanomyces invadans, has spread throughout the world's major continents over the last 50 years, with the apparent exception of South and Central America. With over 160 susceptible fish species representing 54 families and 16 orders recorded to date, EUS is of international concern and infection with A. invadans is a World Organisation for Animal Health (OIE) listed disease. This paper examines what little has been reported on the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…In the present study, we confirmed that A. invadans was a causative agent of epizootic ulcerative syndrome (EUS) in AT Northern Snakeheads. Aphanomyces invadans is the primary causative agent of EUS in nearly 170 species, including wild and farmed freshwater and estuarine fish (Herbert et al 2019; Sumithra et al 2020). This pathogen has been documented in many snakehead species, including the Striped Snakehead Channa striata , Bullseye Snakehead C. marulius (Saylor et al 2010), Spotted Snakehead C. punctata (Hande 2014), and BT Northern Snakehead.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we confirmed that A. invadans was a causative agent of epizootic ulcerative syndrome (EUS) in AT Northern Snakeheads. Aphanomyces invadans is the primary causative agent of EUS in nearly 170 species, including wild and farmed freshwater and estuarine fish (Herbert et al 2019; Sumithra et al 2020). This pathogen has been documented in many snakehead species, including the Striped Snakehead Channa striata , Bullseye Snakehead C. marulius (Saylor et al 2010), Spotted Snakehead C. punctata (Hande 2014), and BT Northern Snakehead.…”
Section: Discussionmentioning
confidence: 99%
“…There was a solitary SVC case in a fishery in 2017 (FHI, 2017). EUS is considered a primarily tropical and subtropical disease (generally requiring temperatures of >20°C for clinical expression) which has caused widespread economic and environmental losses in fresh and brackish water throughout Asia, Africa and North America (Herbert et al ., 2019). It has a prolific host range; officially 94 species can be naturally infected (OIE, 2019), but further evidence suggests that c .…”
Section: Discussionmentioning
confidence: 99%
“…Infection with Aphanomyces invadans is a serious disease of freshwater fishes that is characterized by the presence of oomycete hyphae and necrotizing ulcerative lesions, leading to pathognomonic granulomatous response 1 , 2 . The disease, commonly known as epizootic ulcerative syndrome (EUS), was first reported from ayu in Japan 3 and has subsequently been reported from 20 countries across 4 continents 1 and the disease is spreading to newer areas 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The disease, commonly known as epizootic ulcerative syndrome (EUS), was first reported from ayu in Japan 3 and has subsequently been reported from 20 countries across 4 continents 1 and the disease is spreading to newer areas 4 6 . To date, more than 160 species of fish have been reported to be susceptible to A. invadans 2 and the host range is expanding 7 10 . Furthermore, it is believed that many more species are likely to be susceptible to A. invadans infection 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation